Black Bear GPS Location Data - DeMars, Craig A.; Boutin, Stan (Dryad Digital Repository, 2017)
csv file containing GPS location data of black bears in northeast British Columbia. Data have been cleaned as per the methods outlined in the Journal of Animal Ecology paper.